MENINGKATKAN KEMAMPUAN MENGENAL LIMA HURUF VOKALMELALUI MEDIA BOLA HURUF PADA ANAK USIA 5-6 TAHUN KELOMPOK B DI TKIT JUARA TANJUNG TIRAM KABUPATEN BATU BARA - Nurhikmah Pohan, Nilam Fauzi (Cybernetics: Journal Educational Research and Social Studies, 2020)
This research is motivated by the difficulties of children aged 5-6 years at TKIT Champion Tanjung Tiram in recognizing five vowels, namely children often find it difficult to mention and distinguish vowels such as "e", "u" and the letter "o". While the letters that are always remembered by children are the letter "i" and the letter "a". This study aims to describe the learning process using letter ball media in order to improve children's ability to recognize five vowels at the age of 5-6 years and to determine the increase in children's ability to recognize vowels at the age of 5-6 years at TKIT Champion Tanjung Tiram. The method used in this research is in the form of Classroom Action Research (CAR), which consists of Pre-Cycle, Cycle I, Cycle II and Cycle III. Data collection techniques in this study used observation, interviews, non-test assessment, and documentation. The analysis technique uses descriptive qualitative and quantitative analysis.As for the results of this study, the authors can note that the ability of children aged 5-6 years at TKIT Champion Tanjung Tiram are still many who do not or do not know the five vowels. And the author took the initiative to be able to create a unique learning method associated with the typical way of learning for kindergarten children by playing while learning. In the future, Tanjung Tiram Champion TKIT children will be able to recognize five vowels through learning with letter ball media.